The power of perception: How scientific experts’ understanding of media logic affects their media-related behavior - Birte Leonhardt; Daniel Nölleke; Folker Hanusch (Studies in Communication, Media)
During the COVID-19 pandemic, journalists were heavily reliant on contributions from scientific experts. Despite the often productive collaboration between scientists and journalists, journalistic practices are largely at odds with scientific routines, making scientists not always willing to act as experts in the news media. Against the background of mediatization theory, we argue that their willingness to play by the media rules depends to a large extent on their assessment and understanding of how the news media work. Through in-depth interviews with 24 Austrian scientific experts, we investigated what they perceive as news media logic and how this shapes their responses to media requests. Interviewees exhibited a reflective understanding of news media logic. Findings suggest that experts’ perceptions of how different media work not only affect their decision whether to reject or accept media requests. In addition, they also shape their individual preparation for media engagements.